Cuba em transição: economia e sociedade após uma década de reformas - Nunes, Leon Karlos Ferreira (2021)
After the ascension of Raúl Castro in 2008 and the VI Congress of the Communist Party of Cuba (PCC) in 2011, Cuba has been undergoing a gradual process of economic reforms, generally presented as an update of the development model, generating profound effects in the country's socioeconomic structure, with the rise of new social groups, and, along with them, new subjectivities. Given this situation, a problem arises: how is Cuban society constituted today? The present project arises with the purpose of discussing this issue, especially in a scenario that already adds up to a decade of reforms. As specific objectives, we seek to elaborate a conceptual panorama that allows us to understand the dynamics of Cuban reality (that is, this reality as a historical process) based on classical and contemporary references of historical materialism; identify the material basis of Cuban socialism, based on the country's economic and administrative framework; understand the role of the State in running the country today and in guaranteeing social rights and subsidies; and, finally, to point out the social groups present in the country today, contemplating their hegemonic disputes and emerging subjectivities. Our central hypothesis resides in the premise that emerging social groups are not incompatible with the current model, but as they assume increasing roles in economic life, the pressure for an increasingly intense opening to the market must grow. This study involved bibliographic and documentary research, primary data analysis and semi-structured interviews. Specialized periodicals in the field of social sciences in Cuba were very important, as well as statistical yearbooks on Cuban economy and society. The study demonstrated that, despite the great diversity of actors and perspectives present in Cuban society today and the social inequalities generated by the economic blockade and opening, there are no incompatibilities between the existence of certain social groups and the model of socialism combined with a market that today it is in effect on the island.